ANALISYS OF THE AXIOLOGICAL - SOCIAL, INSTYTUTIONAL AND LEGAL SPHERE OF THE FAMILY POLICY IN SELECTED EU COUNTRIES - Durasiewicz, Arkadiusz (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
The article presents the European models of family policy divided into 5 models - the Scandinavian model, southern European model, conservative, liberal and post-socialist. In each of these the characteristics of policy for families are presented and divided into: axiological conditions, demographic, institutional family support, legal and family policy instruments. An overview of the various issues in the field of family policy is so important that the implementation of the effective family policy contributes to increased fertility, and thus of human capital, social and creative of the country. The article concludes with a summary and recommendations by individual models.